Czech Republic : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1998)
This Selected Issues paper examines recent developments in inflation and its key determinants in the Czech Republic, with particular focus on the role of wages. A simple analytical framework is presented that relates inflation to wages, import prices, and money, and the interaction of inflation with these variables is then examined empirically in the context of a vector autoregression model. The findings confirm the critical influence of wages, exchange rate changes, and money growth. The paper also analyzes developments in the public finance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet